WORKPLACE SPIRITUALITY, HAPPINESS AND SOCIAL SUSTAINABILITY: ANINTEGRATIVE MEDIATED MODEL (CAHIERS MAGELLANES-NS, 2024)
In recent times, a new and promising construct, i.e., workplace spirituality has attracted the attention oforganizational research. Spirituality at workplace is a structure of organisational ethics witnessed intothe culture that enhances the workers experience of transcendence by means of work process; facilitatetheir sense of connection with others in a manner that furnish the feelings of fulfillment as well ashappiness. Creating wholesome organization is a big challenge in this competitive world. One of thefundamental aspects of any organization is happiness of its employees. The employment practices thatpromote workplace happiness are crucial for cultivating a sustainable manpower. In today’s dynamicenvironment, the role of sustainable manpower, which is a crucial asset for the survival of health sector,can’t be neglected. Despite all this, research linking these variables with employees’ well-being is adomain that has not received much attention. The current study is aimed to find out the relationshipbetween spirituality, happiness and social sustainability at workplace among the employees ofhealthcare sector. This study is exploratory-cum-descriptive in nature. A sample of 329 doctors andstaff nurses of multi-specialty hospitals in Haryana was taken using multistage sampling and snowballsampling. A structured questionnaire has been designed to collect the data, and identify what makespeople happy at the workplace and motivate them to do work with full dedication. Smart-PLS 4.0 wasused for processing and analyzing the data. The findings indicate a significant mediating effect ofworkplace happiness in the relation between workplace spirituality and social sustainability. The studyhighlights the significance of applying spirituality at work to enhance the level of happiness among thedoctors and nurses and also offer valuable knowledge about the relation between workplace spirituality,workplace happiness, and social sustainability in health sector